Effect of calcination temperature and atmosphere on crystal structure of BaTiO3 nanofibers - Lee, Deuk Yong; Lee, Myung-Hyun; Cho, Nam-Ihn; Kim, Bae-Yeon; Oh, Young-Jei (KOREAN INST METALS MATERIALS, 2010)
Barium titanate (BaTiO3, BT) nanofibers with a diameter range of 160 nm to 300 nm were prepared by drying electrospun BT/polyvinylpyrrolidone (BT/PVP) composite fibers for 1 h at 80 degrees C in vacuum with a subsequent calcination in air for 1 h at a temperature range of 650 degrees C to 750 degrees C. The morphology and crystal structure of calcined BT nanofibers were characterized with the aid of XRD, FT-IR, SEM, and TEM. The XRD and FR-IR measurements confirm that BT nanofibers with a diameter of about 160 nm and a tetragonal perovskite structure were present in the electrospun fibers after calcination for 1 h at 750 degrees C. The FR-IR analysis of the BT fibers reveals that the intensity level of the O-H stretching vibration bands (at 3430 cm(-1) and 1425 cm(-1)) become weaker as the calcination temperature is increased and that a broad band at 570 cm(-1), which represents the Ti-O vibration, appears sharper and narrower after calcination at 750 degrees C due to the formation of metal oxide bonds. In contrast, BT fibers prepared by a refluxing process in a nitrogen atmosphere show a dramatic change in crystal structure: the tetragonal structure changes to a cubic perovskite structure, probably due to the suppression of carbonate contamination. Thus, the calcination temperature and atmosphere appear to have a significant influence on the crystal structure of BT.